2021
DOI: 10.1007/s42452-021-04244-w
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive control for a class of nonlinear switched systems using state-dependent switching

Abstract: This paper presents a novel adaptive control for a class of nonlinear switched systems by introducing a sufficient condition for stabilization. Based on the possible instability of all sub-systems, a variable structure (VS) switching rule with an adaptive approach and sliding sector was offered. Moreover, the stability condition of the system can be determined by solving linear matrix inequalities (LMIs) to ensure asymptotic stability. The application of H∞ analysis of nonlinear switched systems was also inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…(2) The proposed control scheme restricts the tracking error to a predefined range by introducing an error transformation signal. It should be observed that the adaptive control schemes in References 39 and 40 can only guarantee the stability of the systems without taking into account the predefined performance that is further required by the systems. (3) Furthermore, compared with the time‐triggered schemes in 41 and, 42 we construct an event‐triggered controller, which can reduce the communication burden and improve the utilization of communication channel.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The proposed control scheme restricts the tracking error to a predefined range by introducing an error transformation signal. It should be observed that the adaptive control schemes in References 39 and 40 can only guarantee the stability of the systems without taking into account the predefined performance that is further required by the systems. (3) Furthermore, compared with the time‐triggered schemes in 41 and, 42 we construct an event‐triggered controller, which can reduce the communication burden and improve the utilization of communication channel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the traditional linear control methods have become more and more difficult to satisfy the demand of modern hydraulic systems. To cope with these issues, dozens of advanced nonlinear controllers have been proposed, such as feedback linearization control [5][6][7], nonlinear adaptive control [8][9][10] and adaptive robust control [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, switched systems have received increasing attentions, since such systems can be used to model various control problems and complex processes, such as neural network [5,6], microbial fermentation process [7,8], electronic circuit [9,10], and aircraft control [11,12]. More importantly, when an expected control performance of a complex model is difficult to be achieved by using only a single controller, switching control strategy could be a good choice, which can greatly improve stability and performance [13][14][15][16]. As a consequence, it is of practical importance and theoretical significance to investigate the switching stabilization of switched systems deeply.…”
mentioning
confidence: 99%